Servant Leadership in Nursing Students: Changing to the New Era - Umasawan Chooha; Chakrit Ponathong; Chatupol Yongsorn (Journal of Educational Issues, 2024)
The global pandemic of COVID-19 has resulted in changes in the health service system requiring reliance on new work methods, new cognitive processes and new behavior. Nurses take on key caregiving roles in caring for the entire global population. And in a decade of changes in health services, servant leadership is considered an increasingly important leadership role for nurses. This study aimed to explore servant leadership characteristics among nursing students in this new era. A qualitative thematic analysis of interviews was used to evaluate the key aspects of servant leadership characteristics of nursing students. Data were collected through in-depth interviews with seven subject matter experts from January 2022 to March 2022 in Thailand. Data were analyzed manually using thematic analysis. All seven nursing experts offered the same opinion that the characteristics of servant leadership of nursing students in the new era consisted of seven main characteristics. Nurses should have a nursing mindset expressing personal humbleness with knowledge and nursing practice based on a foundation of professional ethics that make them credible and trustworthy, empowering service recipients as people with far-reaching vision and foresight. Servant leadership is the core of nursing students in the new era, so professors and instructors should foster servant leadership in nursing students in combination with professional practical training to prepare nursing personnel with competence to keep up with changes.